Research Trends in Project-Based Learning in Inclusive Islamic Education: A Bibliometric Analysis Based on Scopus Data - Lismawati Lismawati; Nurul Aisyah; Zahra Irmawiyanti Zahra (Universitas Wahid Hasyim Semarang, 2026)
This study aims to map publication trends, author and country productivity, journal distribution, and the conceptual structure of Project-Based Learning (PjBL) research within inclusive Islamic education through a bibliometric analysis of Scopus data covering 2015–2025. Using a quantitative approach with VOSviewer and R-Biblioshiny instruments, the study analyzed 252 articles meeting the inclusion criteria. Results indicate significant publication growth peaking at 82 articles in 2025, with Indonesia ranking second globally with 75 affiliations (11.3%), and 174 unique journals distributing articles consistent with Bradford's Law. Co-word analysis identified seven thematic clusters, with Islamic Religious Education (PAI) and Islamic values as the most underexplored area (3.9%). Only 7 of 252 articles explicitly integrated Project-Based Learning (PjBL), inclusion, and Islamic Religious Education (PAI) simultaneously, confirming a genuine academic white space. This study recommends developing an integrative Project-Based Learning (PjBL), inclusion, Islamic Religious Education (PAI) framework as a national and global research priority agenda.